Menimbang Kembali Paradigma Filsafat Islam dalam Bangunan Keilmuan Islam Kontemporer - Aksin Wijaya (Ulumuna, 2010)
Islamic philosophy often engaged only in "abstract territory", because it only makes the problems of God as its main object of discussion, while the problems of humanity and modernity that are concretely experienced by human being are neglected. This article aims to discuss and answer some analytical question by using Kuhn’s paradigm of science. The questions are: Is the classical Islamic philosophy of science that is very idealistic and theocentric still relevant to answer the practical problems facing by humanity now? How should we respond to the classical Islamic philosophy? How is "model" of Islamic philosophy that are relevant to the context of Indonesia today? It is found that there are two points that need to be done in order to make classical Islamic philosophy applicable and practical to address contemporary humanity issues: the first is to reconstruct and redefine its structure, and the second to restructure its philosophical building.